Pest forces on agriculture sector / Baderisang Mohamed and Nurul Najiha Azhar - Mohamed, Baderisang; Azhar, Nurul Najiha (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
Agriculture sector is one of the most important sectors in Malaysia and contributes greatly to the Gross Domestic Product (GDP) of the country. According to the Department of Statistics Malaysia, the agriculture sector contributes 7.3% which is RM 99.5 billion to the GDP in 2018. The key contributor to the GDP of the agriculture industry in 2018 is oil palm which is about at 37.9%, followed by livestock at 14.9%, fishing at 12.5%, forestry and logging at 6.9% and rubber at 2.8% (Department of Statistics Malaysia, 2020). Malaysia becomes the highest producer of palm oil and rubber in the world after Indonesia. Agriculture industry has given and provided many job opportunities to both local and foreign workers. Farmers and smallholders, most of who come from low-income household category or B40 enter the agriculture sector to generate income and to raise their livelihood. The government has played its role to increase production to the point of increasing exports, hence, economic growth and agricultural production increased and was able to increase farmers' income indirectly. There are a number of external factors that will impact the agriculture sector which start from political forces, economic forces, social forces, and technology forces or PEST.